Allocation of national renewable expansion and sectoral demand reduction targets to municipal level - Schneider, Simon; Paráda, Edit; Sengl, David; Baptista, José; Oliveira, Paulo Moura (Frontiers in Sustainable Cities, 2024)
Despite the ubiquitous term “climate neutral cities”, there is a distinct lack of quantifiable and meaningful municipal decarbonization goals in terms of the targeted energy balance and composition that collectively connect to national scenarios. In this paper we present a simple but useful allocation approach to derive municipal targets for energy demand reduction and renewable expansion based on national energy transition strategies in combination with local potential estimators. The allocation uses local and regional potential estimates for demand reduction and the expansion of renewables and differentiates resulting municipal needs of action accordingly. The resulting targets are visualized and opened as a decision support system (DSS) on a web-platform to facilitate the discussion on effort sharing and potential realization in the decarbonization of society. With the proposed framework, different national scenarios, and their implications for municipal needs for action can be compared and their implications made explicit.